Karakteristik kriteria ketuntasan minimal (KKM) dalam evaluasi pembelajaran - Abidah, Faizah Nurul (Maliki Interdisciplinary Journal, 2024)
KKM is a standard of learning success set by educational institutions based on graduate competency standards, taking into account the uniqueness of students, subject characteristics and the situation in educational institutions. One of the functions of the Minimum Completeness Criteria (KKM) is as a guide for teachers in assessing students' abilities according to the basic competencies of the subjects being studied. Therefore, teachers must be able to prepare KKM that are appropriate to the subjects being taught. Based on the findings observed by researchers in the previous school year, there are several factors that cause teachers not to be able to determine the KKM well, including: a) teaching methods there is no training regarding setting KKM standards, teachers only estimate the KKM value, and copy paste from the Internet.